Pronoun in Mendriq: Minimalist Programme Analysis: (Ganti Nama Bahasa Mendriq: Analisis Program Minimalis) (Jurnal Bahasa, 2015)
The indigenous languages in Malaysia are heading towards extinction at an alarming rate. Research on these languages is not given proper attention. Therefore, this article will focus on one of the indigenous languages, that is, Mendriq. Mendriq is a language used by the indigenous people living around Kuala Lah, Gua Musang in the state of Kelantan. Research carried out under the UKM-GUP-PLW-08-11-047 research code has a narrow scope whereby it focused merely on the pronouns of the Mendriq language. The analysis of these pronouns is divided into two, descriptive analysis and syntactic analysis. The descriptive analysis discusses the cases in the pronouns of this language. While the syntactic analysis employs the Minimalist Program to analyse the pronouns. Based on this study, the research discovered that the pronouns of Mendriq can be classified into two, i.e. those pronouns that bear cases and pronouns that need to be case marked.Keywords: pronouns, Mendriq, descriptive analysis, syntactic analysis, indigenous, cases